KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VII SMP DANIEL HKBP RUMBAI PEKANBARU - Masita, Masita; Charlina, Charlina; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis Research discussed about the Ability of on Reading Understanding of the first year students at SMP Daniel HKBP Rumbai, Pekanbaru. the Method of this research was descriptive method, which is the data was is explained in research as it is. The technique of this research was test this use technique of tes. this research descriptive about the ability on reading understanding of the first year students at SMP Daniel HKBP Rumbai, Pekanbaru, in aspect of mean indeas, supporting ideas, conclusion, and recommendation of content. the population of this research was 22 students and been the tofal sample. the resvit of this research were (1) the ability on reading understanding in finding mean ideas in medium level, (2) the ability on reading understanding in finding supporting Ideas in lowest level, (3) the ability on reading understanding in finding conclusion in lowest level, and (4) the ability on reading understanding in finding recommendation of content in lowest level. Keyword: Finding mean, Finding suppotting , Finding conclusion, Finding recommendation of conten.